Optically active P-5-deltacyclenes: selective oxidation, ligand properties, and a diastereoselective rearrangement reaction - Keller, Ines Sophie; Bauer, Walter; Heinemann, Frank Wilhelm; Höhn, Christine; Rohwer, Lars; Zenneck, Ulrich (Dalton Transactions, 2016)
Cage-chiral tetra-tert-butyl-P-5-deltacyclene 5 is accessible as a pair of highly enriched enantiomers 5' and 5 ''. The only secondary phosphorus atom P1 of the cage can be selectively oxidized by reaction with t-BuOOH. The P1-oxo species 9a' and 9a '', allow the direct determination of their ee values. Oxidation occurs with the complete retention of the optical activity of the compounds. The chiroptical properties of 9a' and 9a '' are strongly dominated by their cage chirality, the oxygen atom does not contribute significantly. Elemental sulfur and selenium oxidize P5 with high preference to yield P5-thio-and P5-seleno-P5-deltacyclenes 10 and 11 of the intact cages again. Longer reaction time and more than stoichiometric amounts of selenium, leads to tri-seleno-P5-tetracycloundecane 12, a partially opened oxidized rearrangement product. The ligand properties of racemic 9a were determined. Diphosphetane phosphorus atom P2 of 9a is the active donor center to bind a Cr(CO)(5) fragment, but a tautomerization of 9a takes place if [(benzene)RuCl2](2) is added. A hydrogen atom migrates from P1 to the oxygen atom to form a phosphinous acid ligand. The lone pair of P1 is regenerated and acts as the active ligand function of the cage in this case. As for 5, the base n-BuLi induces an efficient cage rearrangement reaction of 9a, where P1 and the neighboring carbon atom C4 containing its t-Bu substituent change places. C4 moves to its new position without breaking the bond with P5, this way forming the novel P1-oxo-P-5-norsnoutene cage in a highly diastereoselective process.